Polymyalgia rheumatica: diagnosis, prescribing, and monitoring in general practice - Helliwell, Toby (Royal College of General Practitioners, 2013)
BACKGROUND: Polymyalgia rheumatica (PMR) is a common rheumatological disorder of older patients. The majority of UK patients are diagnosed and managed exclusively in general practice. In primary care, it has been shown that there is wide variation in practice, and established diagnostic criteria are infrequently used. AIM: This study aims to investigate the diagnostic processes, management, and monitoring of patients with PMR in UK primary care. DESIGN AND SETTING: This is a retrospective cohort study set in primary care. METHOD: Data were extracted from two interlinked primary care databases from north Staffordshire. Patients with PMR were identified using Read Codes and the relevant investigation, prescription, and consultation data were extracted and reviewed. RESULTS: Three hundred and four patients’ records were analysed. Documentation of symptoms leading to a diagnosis of PMR was found in 248 records (81.6%). A documented process of exclusion of relevant differential diagnoses was demonstrated in 68 (22.4%) patients. The mean initial dose of prednisolone was 21.5 mg. Referral to specialist care was made for 135 (44.4%) patients. Gastric prophylaxis was prescribed in 85 (28.0%) cases. Osteoporosis prophylaxis was prescribed to 183 patients (60.2%); 12 patients (3.9%) developed osteoporosis and 56 (18.4%) developed gastric symptoms that led to GP consultation. CONCLUSION: The management of PMR in general practice could be optimised. Identified areas for improvement include clear documentation of a process of exclusion of other diagnoses, and prophylaxis for potential treatment complications, including osteoporosis and gastric symptoms.